Selection and characterization of resistance to the Vip3Aa20 protein from Bacillus thuringiensis in Spodoptera frugiperda. Issue 9 (9th February 2016) - Bernardi, Oderlei; Bernardi, Daniel; Horikoshi, Renato J; Okuma, Daniela M; Miraldo, Leonardo L; Fatoretto, Julio; Medeiros, Fernanda CL; Burd, Tony; Omoto, Celso
Abstract: BACKGROUND: Spodoptera frugiperda is one the main target pests of maize events expressing Vip3Aa20 protein from Bacillus thuringiensis ( Bt ) in Brazil. In this study, we selected a resistant strain of S. frugiperda on Bt maize expressing Vip3Aa20 protein and characterized the inheritance and fitness costs of the resistance. RESULTS: The resistance ratio of the Vip3Aa20‐resistant strain of S. frugiperda was >3200‐fold. Neonates of the Vip3Aa20‐resistant strain were able to survive and emerge as fertile adults on Vip3Aa20 maize, while larvae from susceptible and heterozygous strains did not survive. The inheritance of Vip3Aa20 resistance was autosomal recessive and monogenic. Life history studies to investigate fitness cost revealed an 11% reduction in the survival rate until adult stage and a ∼50% lower reproductive rate of the Vip3Aa20‐resistant strain compared with susceptible and heterozygous strains. CONCLUSION: This is the first characterization of S. frugiperda resistance to Vip3Aa protein. Our results provide useful information for resistance management programs designed to prevent or delay resistance evolution to Vip3Aa proteins in S. frugiperda . © 2016 Society of Chemical Industry